2011
DOI: 10.1007/s10856-011-4345-0
|View full text |Cite
|
Sign up to set email alerts
|

β-Tricalcium-phosphate stimulates the differentiation of dental follicle cells

Abstract: The use of dental progenitor cells is a straightforward strategy for regenerative dentistry. For example a cell based therapy with dental follicle cells (DFCs) could be a novel therapeutic strategy for the regeneration of oral tissues in the future. For the regeneration of large bone defects for example dental progenitor cells have to be combined with bone substitutes as scaffolds. This study therefore investigated cell attachment (scanning electron microscopy), cell vitality/proliferation (WST-1 assay) and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…As we have learned from previous studies mechanical properties such as surface stiffness are decisive for a successful osteogenic differentiation of dental stem cells [13,14]. Moreover, we showed that bone substitute materials such as β-tricalcium phosphate (TCP) supports the osteogenic differentiation [10]. Our study proposed therefore that bone-like materials such as commercially available bone substitutes are superior for dental tissue engineering.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…As we have learned from previous studies mechanical properties such as surface stiffness are decisive for a successful osteogenic differentiation of dental stem cells [13,14]. Moreover, we showed that bone substitute materials such as β-tricalcium phosphate (TCP) supports the osteogenic differentiation [10]. Our study proposed therefore that bone-like materials such as commercially available bone substitutes are superior for dental tissue engineering.…”
Section: Discussionmentioning
confidence: 70%
“…We showed that DFCs had a typical flattened-shaped morphology with close contacts to the bone substitute material [10]. Interestingly, the gene expression of osteogenic markers such as osteopontin or RUNX2 was increased, and the alkaline phosphatase (ALP) activity was induced on TCP in differentiated DFCs [10]. All these data support the assumption that TCP could be the optimal scaffold for a successful differentiation protocol of DFC.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Although newly formed hard tissues were observed in all implants, a dentin-like hard tissue was observed when porous BCP was used [577]. Besides, incorporation of nano-sized HA into electrospun poly(ε-caprolactone)/gelatin scaffolds was found to enhance dental pulp stem cells differentiation towards an odontoblast-like phenotype both in vitro and in vivo [578]. The osteoblast marker bone sialoprotein was highly expressed on β-TCP scaffolds seeded by dental follicle cells but almost absent in differentiated dental follicle cells without β-TCP.…”
Section: Tissue Engineering Approachesmentioning
confidence: 92%